2018
DOI: 10.12788/jcso.0427
|View full text |Cite
|
Sign up to set email alerts
|

Marriage predicts for survival in patients with stage III non–small-cell lung cancer

Abstract: Background Comprehensive analysis of prognostic significance of marital status in patients with stage III non-small-cell lung cancer (NSCLC) when adjusted for patient-, disease-, and treatment-specific factors, including the interaction with racial, nutritional, and immunologic status, is lacking. Objective To evaluate whether marital status is an independent predictor of clinical outcomes in patients with stage III NSCLC who are treated uniformly with curative intent. Methods The Kaplan-Meier method and Cox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…Conversely, unmarried Arab men had lower risk of mortality, in contrast to previous studies which demonstrated higher mortality among unmarried men ( Vyfhuis, 2018 ). Similar to unmarried Arab women, in such a traditional society where marriage is an important aspect of family life, Arab men who remain unmarried may not conform to societal norms.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Conversely, unmarried Arab men had lower risk of mortality, in contrast to previous studies which demonstrated higher mortality among unmarried men ( Vyfhuis, 2018 ). Similar to unmarried Arab women, in such a traditional society where marriage is an important aspect of family life, Arab men who remain unmarried may not conform to societal norms.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, a study conducted in the U.S. found that married men but not women, have a higher chance of survival. It is posited that marriage serves as a proxy for a stronger support system, which has been proven to positively affect survival ( Vyfhuis, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The NCDB lacks any information on patient selection, staging studies (positron emission tomography/computed tomography (PET/CT), brain imaging) or salvage treatments given. It is certainly possible that patients who were considered for upfront surgical resection had more favorable demographic characteristics not reported in the NCDB, such as improved performance status, pulmonary function reserve, or social support, all of which can influence outcomes in lung cancer ( 12 , 13 ). Furthermore, mediastinal assessment and clearance with a lung cancer diagnosis is imperative, as it strongly correlates with survival ( 14 - 16 ).…”
mentioning
confidence: 99%